232k views
5 votes
Using the Constant Multiple Rule, complete the table to find the derivative of the function without using the Quotient Rule.

Using the Constant Multiple Rule, complete the table to find the derivative of the-example-1

1 Answer

5 votes

ANSWER:


\begin{gathered} \text{ Rewrite} \\ \\ y=(10)/(3)(1)/(x^(3)) \\ \\ \text{ Differentiate} \\ \\ y^(\prime)=(10)/(3)(-3x^(-4)) \\ \\ \text{ Simplify} \\ \\ y^(\prime)=-(10)/(x^(4)) \end{gathered}

Explanation:

We have the following expression:


y=(10)/(3x^3)

We rewrite and we would have:


y=(10)/(3)\left((1)/(x^3)\right)

Now we derive:


\begin{gathered} y^(\prime)=(10)/(3)(d)/(dx)\left((1)/(x^3)\right) \\ \\ y^(\prime)=(10)/(3)\left(-3x^(-3-1)\right) \\ \\ y^(\prime)=(10)/(3)(-3x^(-4)) \end{gathered}

Finally, we simplify


\begin{gathered} y^(\prime)=(10)/(3)(-3x^(-4))=-10x^(-4) \\ \\ y^(\prime)=-(10)/(x^4) \end{gathered}

User Harsimran Singh
by
5.6k points